11/22/63 : a novel - King, Stephen, 1947- (New York : Scribner, 2011)
King sweeps readers back in time to another moment, a real life moment, when everything went wrong: the JFK assassination. And he introduces readers to a character who has the power to change the course of history.
Maine author. Stephen King has a residence in Bangor, ME.
Keywords: Kennedy, John F. -- 1917-1963 -- Assassination -- Fiction; Time travel -- Fiction; Alternative histories (Fiction)